2020
DOI: 10.3389/fmed.2020.580796
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and Furin Expressions in Oral Epithelial Cells Possibly Facilitate COVID-19 Infection via Respiratory and Fecal–Oral Routes

Abstract: Background: Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that mainly transfers from human to human via respiratory and gastrointestinal routes. The S-glycoprotein in the virus is the key factor for the entry of SARS-CoV-2 into the cell, which contains two functional domains: S1 is an angiotensin-converting enzyme 2 (ACE2) receptor binding domain, and S2 is necessary for fusion of the coronavirus and cell membranes. Moreover, it has been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 45 publications
3
71
0
1
Order By: Relevance
“…While SARS-CoV-2 infection is noted in oral cavity, in salivary glands, gingiva, oral mucosa and saliva 16 , no one has yet published on taste tissue. Furthermore, previous studies 16 , 26 , 27 did not address the cellular location of ACE2 within human taste buds using the highly specific techniques of ISH (mRNA) and IFS (protein). Taste buds do not contain a resident immune system 28 and TRCs account for all cells within taste buds.…”
Section: Discussionmentioning
confidence: 99%
“…While SARS-CoV-2 infection is noted in oral cavity, in salivary glands, gingiva, oral mucosa and saliva 16 , no one has yet published on taste tissue. Furthermore, previous studies 16 , 26 , 27 did not address the cellular location of ACE2 within human taste buds using the highly specific techniques of ISH (mRNA) and IFS (protein). Taste buds do not contain a resident immune system 28 and TRCs account for all cells within taste buds.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ACE2 in the tongue, lip, and cheek has been stated by Sawa [73]. Chen et al discovered that ACE2 is expressed in salivary glands [74]. Finally, the immunohistochemistry results reported by Zhong et al showed that the anatomical areas with the highest expression of ACE2 from highest to lowest were lip, tongue, buccal mucosa, and gingival and palatal tissue.…”
Section: Ace2 Expression In T2dmmentioning
confidence: 83%
“…The expression and distribution of ACE2 in the human body may indicate potential SARS-CoV-2 infection routes, which have major implications for understanding pathogenesis and designing therapeutic strategies [67]. Some studies have shown that ACE2 is potentially expressed in the oral cavity and is highly enriched in epithelial cells [68][69][70][71][72][73][74][75]. According to Xu et al, ACE2 expression was shown to be slightly higher in the oral tongue than in other oral tissues.…”
Section: Ace2 Expression In T2dmmentioning
confidence: 99%
“…Only one study focused on identifying the presence of SARS-CoV-2 in oral tissues by means of PCR. The study design most used was “in silico”, followed by “in vivo” and finally “in vitro” [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Most of the articles showed a combination of two or more of the aforementioned study designs.…”
Section: Resultsmentioning
confidence: 99%